HUKUM PERSAINGAN USAHA DI INDONESIA DIKAITKAN DENGAN SISTEM EKONOMI KERAKYATAN - syamsah, tn (Universitas Djuanda Bogor, 2011)
While the whole world sees the market economy is the best system in political, economical, and cultural now a day, but the system itself cannot make a significant contribution to peopleÃ¢â¬â¢s welfare. In fact, USA as a founding and the leader of the system, at some point cannot implement the system completely. The country still protect some of their important business areas such as bank, flight, train, public facility, telephone, advertisement, broadcast, medical services and agriculture. The national budget of the country shows that subsidise for agriculture sector alone is almost 50% from national budget. The regulation relates to economy of the country indicates that strong protection for almost industry sector. This policy indicates that somehow a country cannot avoid protect its certain economy sector that become the countryÃ¢â¬â¢s strength. Indonesia as a country that its economy based on agriculture should consider the better protection for this very important sector. In this sense, it looks that people economy approach is best suit to current Indonesia situation.Â